Optimized Control and Power Sharing in Microgrid Network - Jouda, Mohammed Said; Kahraman, Nihan (IEEE, 2019)
The synchronization and power-sharing among parallel inverters beside the voltage stability and frequency are important functions to be achieved in the microgrid. This paper investigates power sharing and controller is applied to limit voltage and frequency deviation. The voltage and frequency stability can be improved using a droop control with optimization technique for power (active and reactive) sharing of parallel distributed generation (DG) units. Where conventional droop control is not accurate share of output current and power among inverters. Therefore, particle swarm optimization (PSO) is a smart control strategy to reduce the frequency and voltage deviation, reduce the harmonic current, and it can accurately power sharing with elimination a mismatched among inverters or DG. The results of the control strategies are verified in simulation using Matlab/Simulink.
Keywords: Microgrid; droop control; power sharing; particle swarm optimization; INVERTERS; Computer Science; Engineering